Exploration of Local Wisdom-Based Tourism Potential in Cikakak Banyumas Tourism Village - Sayudin (Politeknik Siber Cerdika Internasional, 2025)
This study aims to explore the potential of local wisdom-based tourism in Cikakak Tourism Village, Banyumas, and identify factors that can improve the success of sustainable tourism management. The method used was a qualitative approach with a case study design, which involved in-depth interviews with tourism village managers, local communities, and tourists, as well as participatory observation of tourism activities in the village. The results showed that local wisdom, such as traditional arts, handicrafts, and sustainable natural resource management, are the main assets of the tourism village. However, the major challenges faced are limited infrastructure, lack of training for the community, and low awareness of the importance of cultural and natural preservation. This research recommends increasing the capacity of tourism village managers, empowering local communities, and developing infrastructure to support more sustainable and inclusive tourism activities. The implications of this research are expected to provide practical guidance for tourism village managers in developing sustainable local wisdom-based tourism.